Pengaruh Motivasi Kerja Terhadap Kualitas Layanan Publik Kantor Disdikpora Kabupaten Buleleng - Nyoman Dewi Purnamasari; Helvoni Mahrina (Jurnal Pendidikan Ekonomi Undiksha, 2025)
Good service quality and results can be influenced by strong work motivation, and vice versa. If work motivation is low, the public service process will also have poor results. Quantitative research methodology was used in this work. Data collection techniques included questionnaires, recording, and observation. Using a Simple Random Sampling approach, the research data source was the population, consisting of 32 people. To find significant findings between the two variables related to work motivation and public service, a simple regression calculation was used. The researcher then conducted reliability and validity tests. Based on this study, public service at the Buleleng Regency Education Office is strongly influenced by work motivation. Therefore, work motivation plays a role in public service at the Buleleng Regency Education Office, because increasing work motivation will impact the public service provided by the organization.